Discriminating detection of multiple analytes (F− and CN−) by a single probe through colorimetric and fluorescent dual channels. (December 2015) - Wang, Ying; Zhao, Qian; Zang, Libin; Liang, Chunshuang; Jiang, Shimei
Abstract: Two novel Schiff base type receptors containing phenol hydroxyl group (1 ) or methoxy group (2 ) were designed and synthesized. The receptor1 with phenol hydroxyl group exhibited different colorimetric and fluorimetric responses to fluoride and cyanide ions. In the colorimetric channel, the colorless solution turned to yellow towards F −, but red in the presence of CN − . In the fluorimetric channel, the nonluminous solution showed different "turn-on" response to F − and CN −, respectively. The distinguishing responses of receptor1 to the two anions in dual channels were attributed to the disparate interaction mechanisms. F − was detected through the formation of hydrogen bonds and the subsequent deprotonation process. CN − initially formed hydrogen bonds and then it attacked the receptor via a nucleophilic addition reaction. In contrast, the receptor2 with methoxy group only showed remarkable color change from colorless to yellow towards F − . These results proved that the phenol hydroxyl group played an important role in the discriminating detection of F − and CN − . Graphical abstract: A new "one to more" type sensor has been developed for the selective and discriminating detection towards F − and CN − through the colorimetric and fluorescent channels, which was based on the different mechanisms for the two anions. Highlights: A simple receptor towards fluoride and cyanide with high selectivity was developed. The receptor responses to F − and CN − in different channels, respectively. The discriminating detection was attributed to the disparate interaction mechanism.